2017
DOI: 10.1080/17458080.2017.1357842
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature synthesis of multiwalled carbon nanotubes and incorporation into an organic solar cell

Abstract: Metal nanoparticle (MNP) catalysts used for the synthesis of multiwalled carbon nanotubes (MWCNTs) consisted of single metals (Fe, Ni or Co) and bimetallic mixture (CoFe, NiFe or NiCo). MWCNTs were successfully synthesised at 200 C in 10 min using liquefied petroleum gas as carbon source with non-equilibrium plasma enhanced chemical vapour deposition (PECVD) method. The nanostructures and the morphology of the MNPs and the MWCNTs film were characterised using relevant microscopic and spectroscopic methods. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…TCVD strategies include: choice of carbon feedstock [119,131], solution processed catalyst [134,136], multilayered catalyst [122], support layer [128], Oxidative dehydrogenation [120], Novel catalyst materials [135] and multi-temperature-zone chambers [179]. PECVD strategies are: choice of Carbon feedstock [147], solution processed catalyst [159], multilayered catalyst [157], size-classified catalyst [138], support layer [137], Oxidative dehydrogenation [156], remote plasma [100,139] and pulse power [141,153]. PTCVD strategies are: support layer [79], carbon source [77], rapid-growth process [60], maximizing energy coupling by optimising underlayers [79] and protected catalyst method [56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TCVD strategies include: choice of carbon feedstock [119,131], solution processed catalyst [134,136], multilayered catalyst [122], support layer [128], Oxidative dehydrogenation [120], Novel catalyst materials [135] and multi-temperature-zone chambers [179]. PECVD strategies are: choice of Carbon feedstock [147], solution processed catalyst [159], multilayered catalyst [157], size-classified catalyst [138], support layer [137], Oxidative dehydrogenation [156], remote plasma [100,139] and pulse power [141,153]. PTCVD strategies are: support layer [79], carbon source [77], rapid-growth process [60], maximizing energy coupling by optimising underlayers [79] and protected catalyst method [56].…”
Section: Discussionmentioning
confidence: 99%
“…In the first step, they deposited 30 nm catalyst film comprising Fe, Ni and Cr at 300°C by striking plasma for 10 min using 500 W rf power and Ar/ H 2 mixture, and then they carried out CNT growth for 100 min in the temperature range of 400-500°C, using C 2 H 2 as carbon feedstock and 30 W rf power. Growth of vertically aligned CNTs with lengths from 0.9 to 6.0 μm is reported in this study.Mugadza et al reported PECVD growth of MWCNTs on indium tin oxide (ITO) coated glass substrate at 200°C and their incorporation into solar cells [159]. They prepared monometallic and bimetallic catalyst nanoparticles from the respective metal chlorides by solution process involving several steps.…”
Section: Cnt Growth Using Plasma Enhanced Cvdmentioning
confidence: 99%
“…Recently, carbon-based materials, such as ITO/ MWCNT, 152 SWCNT, 153 Au-CNT, 154 polymeric acid (PA)-CNT 155 and CNT/AgNW, 156 Table 8. However, these values were lower than those for the ITO reference devices, and this was attributed to the relatively low optical transmittance and high sheet resistance of the CNT-based electrodes, which respectively, reduced the passage of incoming light into the cell, thereby reducing exciton generation, and lowered the mobility of the photo-generated carriers, thereby reducing J sc .…”
Section: Oscs Based On Other Carbon-based Materialsmentioning
confidence: 99%
“…Recently, carbon‐based materials, such as ITO/MWCNT, 152 SWCNT, 153 Au‐CNT, 154 polymeric acid (PA)‐CNT 155 and CNT/AgNW, 156 have been employed as electrodes in OSCs. The resulting ITO/MWCNT/PEDOT:PSS/P3HT:PCBM/LiF/Al, SWCNT/MoO x /PEDOT:PSS/3,6‐bis[5‐(benzofuran‐2‐yl)thiophen‐2‐yl]‐2,5‐bis(2‐ethylhexyl)pyrrolo[3,4‐c]pyrrole‐1,4‐dione (DPP(TBFu) 2 ):PCBM/LiF/Al, CNT/PEDOT:PSS/P3HT:PCBM/biuret/eutectic gallium‐indium (EGaIn), PA‐CNT/MoO 3 /PEDOT:PSS/PBTZT‐stat‐BDTT‐8:PC 71 BM/LiF/Al and CNT‐AgNW/PEDOT:PSS/P3HT:PCBM/LiF/Al OSCs displayed PCEs of 0.68%, 1.90%, 2.74%, 8.00% and 2.21%, respectively, as shown in Table 8.…”
Section: Oscs Based On Other Carbon‐based Materialsmentioning
confidence: 99%
“…Most of these applications require a particular type of CNMs to be highly efficient. Hence, a wide range of shaped CNMs have been reported, including spheres [ 12 ], fibers [ 13 ], ribbons [ 14 ] and tubes [ 15 ].…”
Section: Introductionmentioning
confidence: 99%